The feedback process: Perspectives of first and second year undergraduate students in the disciplines of education, health science and nursing - Douglas, Tracy; Salter, Susan; Iglesias, Miguel; Dowlman, Michele; Eri, Raj (Journal of University Teaching and Learning Practice, 2016)
The purpose of this study was to determine the current perspectives of feedback from first and second year undergraduate students enrolled in blended units of study which incorporated both face-to-face and online components. Students enrolled in a unit of study taught by the School of Health Sciences at the University of Tasmania were surveyed to broadly determine their perception of the feedback process. Responses from the 55% of the cohort who completed the survey indicated that students recognised a wide variety of feedback processes in both written and online formats. Results indicated that students did not always identify that feedback (particularly formative) could feed forward to enhance their learning. There was a strong student focus on the importance of summative assessment feedback. The analysis of survey responses identified four main themes which form the focus of the discussion; types of feedback, student role in seeking feedback, the usefulness of feedback to learning and, feedback perception and awareness of students. The outcomes of this study also highlighted the necessity to educate both teaching staff and students with respect to feedback processes within the learning and teaching paradigm in higher education.